Teacher Enthusiasm and EFL Learners’ Willingness to Communicate: The Role of Enjoyment and Boredom - Fallah, Nasser; Gaskaree, Behruz Lotfi; Moghaddam, Sajjad Zahedi (English teaching & learning, 2025)
The aim of this study was to investigate the interconnections among perceived teacher enthusiasm (TE), foreign language enjoyment (FLE), academic boredom, and willingness to communicate (WTC) among undergraduate EFL (English as a foreign language) learners in Iran. Further, the mediating impacts of boredom and FLE on TE-WTC connection were tested. Accordingly, 291 EFL students were invited through convenience sampling and requested to fill out self-report surveys. Validity and reliability of the questionnaires were examined. The results of structural equation modeling analysis indicated that TE could positively predict FLE and WTC and inversely predict boredom. Further, FLE positively and significantly predicted WTC. However, boredom could only indirectly affect WTC through the mediation of FLE. Another line of the findings revealed that FLE but not boredom mediated the impact of TE on WTC. Theoretical and empirical implications were discussed, and suggestions were made for future research.